2023
DOI: 10.3389/fbioe.2023.1184973
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking cellular barriers: silica nanoparticles and fullerenol conjugated cell-penetrating agents for enhanced intracellular drug delivery

Abstract: The limited delivery of cargoes at the cellular level is a significant challenge for therapeutic strategies due to the presence of numerous biological barriers. By immobilizing the Buforin II (BUF-II) peptide and the OmpA protein on magnetite nanoparticles, a new family of cell-penetrating nanobioconjugates was developed in a previous study. We propose in this study to extend this strategy to silica nanoparticles (SNPs) and silanized fullerenol (F) as nanostructured supports for conjugating these potent cell-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…SiNPs could probably lessen the A. veronii –induced ROS by penetrating smoothly through renal and hepatic cells, reflecting antioxidant protection. These findings were supported by Ravelo-Nieto et al ( 2023 ), who declared that SiNPs are safe, perfect penetrating agent that can easily pass through biological membranes without influencing the viability of cells. A similar report by Mahboub et al ( 2022b ) found that SiNPs can alleviate the histopathological changes induced by heavy metal toxicity in C. gariepinus .…”
Section: Discussionmentioning
confidence: 58%
“…SiNPs could probably lessen the A. veronii –induced ROS by penetrating smoothly through renal and hepatic cells, reflecting antioxidant protection. These findings were supported by Ravelo-Nieto et al ( 2023 ), who declared that SiNPs are safe, perfect penetrating agent that can easily pass through biological membranes without influencing the viability of cells. A similar report by Mahboub et al ( 2022b ) found that SiNPs can alleviate the histopathological changes induced by heavy metal toxicity in C. gariepinus .…”
Section: Discussionmentioning
confidence: 58%